Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4238/2015.december.9.14
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL6 polymorphism and risk of cerebral infarction

Abstract: ABSTRACT. We conducted a case-control study to investigate the influence of IL6 -174G/C (rs1800795) and -572C/G (rs1800796) genetic variants on the development of cerebral thrombosis in a Chinese population. This study included 305 cerebral infarction patients and 326 control subjects enrolled between May 2012 and May 2014. The genotyping of IL6 -174G/C (rs1800795) and -572C/G (rs1800796) polymorphisms was performed using polymerase chain reaction combined with restriction fragment length polymorphism analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The risk of CI may vary according to the presence of various genetic and environmental factors. In addition, the relationship between the functional variation of multiple gene in different ethnic groups and CI risk has been studied, including the polymorphisms of interleukin-6 gene [ 2 ], β-fibrinogen gene [ 3 ], PON1 hypermethylation and PON3 hypomethylation [ 4 ], 5-lipoxygenase-activating protein gene association (ALOX5AP) [ 5 ], the cytochrome P450 1A1 (CYP1A1) gene [ 6 ], the human scavenger receptor class B type I (SR-BI) gene [ 7 ], genes associated with lipid metabolism [ 8 , 9 ], and others [ 10 ]. In general, it is important for both risk prediction and prevention of CI by identifying genetic risk.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of CI may vary according to the presence of various genetic and environmental factors. In addition, the relationship between the functional variation of multiple gene in different ethnic groups and CI risk has been studied, including the polymorphisms of interleukin-6 gene [ 2 ], β-fibrinogen gene [ 3 ], PON1 hypermethylation and PON3 hypomethylation [ 4 ], 5-lipoxygenase-activating protein gene association (ALOX5AP) [ 5 ], the cytochrome P450 1A1 (CYP1A1) gene [ 6 ], the human scavenger receptor class B type I (SR-BI) gene [ 7 ], genes associated with lipid metabolism [ 8 , 9 ], and others [ 10 ]. In general, it is important for both risk prediction and prevention of CI by identifying genetic risk.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the abovementioned studies indicate that role of IL-6 in the pathomechanism of inflammatory response in various forms of cerebral infarction could be more complex than previously assumed and confirm the need for further studies, both in the experimental models and clinical settings. The relationship between IL-6 gene polymorphism and increased risk of cerebral infarction has been suggested [176,177], although this was not confirmed by the other published results and further studies of this issue are required [178].…”
Section: Interleukin-6mentioning
confidence: 77%
“…It has been shown that SNPs of IL-6 may influence the development of cardiovascular disease, 28 cancer, 29 30 fractures 31 and autoimmune diseases. [32][33][34] In contrast, there is less available research regarding TIE2 gene polymorphisms, except for a study on the relationship between rs638203/rs639225 and vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported its association with venous malformation and presumed that this polymorphism might cause abnormal splicing of TIE2 into a defective protein. 28 Functional validation of this polymorphism is warranted in the future.…”
Section: Discussionmentioning
confidence: 99%